Cost of capital in Brazil: a methodological approach (Revista de Administração, 2008)
The Capital Asset Pricing Model (CAPM) offers valid and accepted concepts in the definition of the assets risks. This is measured by the relation between the market return covariance and the company return variance. The methodology applied for the CAPM model is based on stable markets, so the favorable conclusions for it must be re-evaluated for emergent markets, as the Brazilian market. This paper discusses the Brazilian market's main financial indicators justified by statistical means, the inconsistency of the results, revealing the need to verify the Brazilian investor's opportunity cost using the benchmark of a more stable economy. So, the objective of this paper is to suggest a model using benchmark standards, by the description of the several necessary adjustments to calculate the investor's opportunity cost of the Brazilian companies. The capital cost model suggested incorporates, besides the country risk, the volatility of the Brazilian shareholding market.